Usual consumption of ultra-processed foods and its association with sex, age, physical activity, and body mass index in adults living in Brasília City, Brazil - Clíslian Luzia da Silva; Alessandra Gaspar Sousa; Lara Pereira Saraiva Leão Borges; Teresa Helena Macedo da Costa (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2021)
ABSTRACT: Objective: To evaluate the usual consumption of ultra-processed foods (UPF) and its association with body mass index (BMI), physical activity (PA), age, and sex in adults living in Brasília City, Brazil. Methodology: A total of 506 individuals aged ≥ 20 years old were interviewed. Dietary intake was assessed with two non-consecutive 24-h food recalls. The distributions of usual intakes of energy and the amount of UPF were estimated using the Iowa State University method. The association of age, BMI, PA, and sex with the proportions of UPF consumption (%Kcal and %grams) was investigated with linear regression models. Results: UPF represented 9.2% of the total dietary consumption (grams/day) and 25% of total energy intake. Compared to eutrophic, subjects with obesity consumed a higher percentage of UPF in grams, whereas subjects with overweight had a higher percentage of UPF in kilocalories. The share of UPF in energy intake was lower in male than female individuals, and PA and age were inversely associated with UPF consumption. Conclusion: Careful monitoring of intake of UPF is recommended. Its consumption should be reduced among people with overweight/obesity and sedentary individuals. Appropriate choices for methods to evaluate the usual distribution of intake will strengthen future analysis of UPF assessment.